Pengaruh Penerimaan Pajak Daerah, Retribusi Daerah dan Dana Bagi Hasil Terhadap Alokasi Belanja Modal Kabupaten/Kota di Provinsi Jambi Tahun 2013 - 2017 - Debby Santy S; Amri Amir; Ilham Wahyudi (Jurnal Akuntansi & Keuangan Unja, 2020)
This study aimed to analyze the effect of Regional Tax Receipts, Regional Levies and Profit Sharing Funds simultaneously and partially on the capital expenditure allocation of Regencies/Cities Governments in Jambi Province. The subjects in this study were all Regencies/Cities Governments in Jambi Province. The data were collected in this study were secondary data in the form of regional financial data, namely Regional Tax Revenues, Regional Retributions and Revenue Sharing Reports of Realization of Regional Revenues and Expenditures Budget of Regencies/Cities Governments in Jambi Province. Data analysis in this study used panel data analysis. The results of this study indicated that local tax revenues, local retribution, and profit sharing funds simultaneously have significant effect on the allocation of capital expenditures which means that together local tax revenues, regional retribution, and revenue sharing funds were able to explain well the capital expenditure allocation of Regencies/Cities Governments in Jambi Province. The results of this study also showed that regional taxes and profit sharing funds have a positive and significant effect on the capital expenditure allocation, while regional retribution does not have a significant effect on the capital expenditure allocation of Regencies/Cities Governments in Jambi Province.